2017
DOI: 10.1007/s11356-017-9728-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for photolytic and microbial degradation processes in the dissipation of leptospermone, a natural β-triketone herbicide

Abstract: Bioherbicides appear as an ecofriendly alternative to synthetic herbicides, generally used for weed management, because they are supposed to have low side on human health and ecosystems. In this context, our work aims to study abiotic (i.e., photolysis) and biotic (i.e,. biodegradation) processes involved in the fate of leptospermone, a natural β-triketone herbicide, by combining chemical and microbiological approaches. Under controlled conditions, the photolysis of leptospermone was sensitive to pH. Leptosper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
1
0
1
Order By: Relevance
“…reported that roflamycoin, an antifungal metabolite produced by Streptomyces roseoflavus, was degraded under the sunlight as well as under fluorescent light. Photo-oxidation of natural compounds by UV, including biocontrol products, has been reported by Ahonsi et al (2006) and Romdhane et al (2018). Plant parameters may also be involved in the differences observed between both experiments.…”
Section: Screening For Anti-oomycete Activitymentioning
confidence: 83%
“…reported that roflamycoin, an antifungal metabolite produced by Streptomyces roseoflavus, was degraded under the sunlight as well as under fluorescent light. Photo-oxidation of natural compounds by UV, including biocontrol products, has been reported by Ahonsi et al (2006) and Romdhane et al (2018). Plant parameters may also be involved in the differences observed between both experiments.…”
Section: Screening For Anti-oomycete Activitymentioning
confidence: 83%
“…Com a grande comercialização desses compostos como herbicidas, vários estudos já foram realizados para avaliar o impacto ecotoxicológico de β-tricetonas naturais e sintéticas na diversidade da comunidade bacteriana, sendo demonstrado que a dissipação da leptospermona e sulcotriona ocorre dentro de 45 dias no solo (CALVAYRAC et al, 2012;ROMDHANE et al, 2016;ROMDHANE et al, 2019). Nesse mesmo sentido, Romdhane et al ( 2019) afirmam também que a leptospermona e sulcotriona apresentaram meia-vida semelhante quando usadas em dose agronômica, enquanto que ao usar uma dose mais alta, a leptospermona apresentou uma meia-vida mais curta que sulcotriona, confirmando que um composto natural é mais facilmente biodegradável do que um sintético (ROMDHANE et al, 2018).…”
Section: -β-Tricetonasunclassified